Legal Analysis for the Child Those Born Outside the Registry - Nur Fadhilah Rahmattika; Nur Moahamad Kasim; Julisa Aprilia Kaluku (Universitas Negeri Gorontalo, 2022)
This research was carried out at the Suwawa Religious Court Office as well as places related to the author's discussion. This study aims to determine the factors that cause the occurrence of a right for a child born from an unregistered marriage. Primary data and secondary data were collected and analyzed based on a descriptive qualitative problem formulation. Already pregnant out of wedlock, 2) Not getting permission for polygamy, 3) lack of attention or knowledge of the importance of having a legal marriage in the eyes of the law.